2007
DOI: 10.3748/wjg.v13.i27.3756
|View full text |Cite
|
Sign up to set email alerts
|

An unreported complication of acute pancreatitis

Abstract: Acute pancreatitis constitutes 3% of all admissions with abdominal pain. There are reports of osteal fat necrosis leading to periosteal reactions and osteolytic lesions following severe pancreatitis, particularly in long bones. A 54-year-old man was admitted to our hospital with acute pancreatitis, who later developed spinal discitis secondary to necrotizing pancreatitis. He was treated conservatively with antibiotics and after a month he recovered completely without any neurological deficit. This case is repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…9,10 Besides our patient, there is only one other case of spinal discitis associated with pancreatitis reported in the literature. 25 Prompt recognition of PPP syndrome is critical to drive treatment toward the pancreatic condition and prevention of sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Besides our patient, there is only one other case of spinal discitis associated with pancreatitis reported in the literature. 25 Prompt recognition of PPP syndrome is critical to drive treatment toward the pancreatic condition and prevention of sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…There are 25 well-documented case reports of 'PPP syndrome' consisting of pancreatitis, panniculitis and polyarthritis in literature. 9 Muthukumarasamy et al 10 have reported a case of spinal discitis associated with pancreatitis. Very rarely, multiple aseptic subcutaneous fat necrosis, prolonged fever, polyarthritis, polyserositis, vasculitis and eosinophilia, isolated or in combination, may appear during the disease process.…”
Section: Discussionmentioning
confidence: 99%